S-alleles in self-compatible Prunus webbii - Sánchez A.M.; Oliveira M.M. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
Introducing self-compatibility has long been an objective of almond breeders and numerous programmes have used 'Tuono', a self-compatible almond variety, for this purpose. 'Tuono' is thought to have arisen from a cross between almond and P. webbii, a wild relative of almond described as self-compatible. Recently the Sf allele has been identified in 'Tuono' and this allele seems to segregate with self-compatibility. Apparently no RNase activity is linked to Sf but the actual causes of self-compatibility remain unknown. In order to gain insight on the mechanisms behind self-compatibility we have been studying the self-compatible P. webbii. Not only has the Sf allele been identified in two individuals but also new S-sequences were isolated. It remains to be seen if these putative S-alleles are also non-functional (as Sf seems to be) or if the cause of self-compatibility lies elsewhere and new strategies for obtaining self-compatible almonds may be devised.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)